Gender, age‐related, and regional differences of the magnetization transfer ratio of the cortical and subcortical brain gray matter. Issue 2 (29th October 2013) - Mascalchi, Mario; Toschi, Nicola; Ginestroni, Andrea; Giannelli, Marco; Nicolai, Emanuele; Aiello, Marco; Soricelli, Andrea; Diciotti, Stefano
<x xml:space="preserve">Abstract</x> Purpose To explore gender, age‐related, and regional differences of magnetization transfer ratio (MTR) of brain cortical and subcortical gray matter (GM). Materials and Methods In all, 102 healthy subjects (51 women and 51 men; range 25–84 years) were examined with 3‐mm thick MT images. We assessed MTR in automatically segmented GM structures including frontal, parietal‐insular, temporal, and occipital cortex, caudate, pallidus and putamen, and cerebellar cortex. A general linear model analysis was conducted to ascertain the linear and quadratic relationship among the MTR and gender, age, and anatomical structure. Results The effect of gender was borderline (P = 0.07) in all GM structures (with higher MTR values in men), whereas age showed a significant linear as well as quadratic effect in all cortical and subcortical GM structures (P ≤ 0.001). Quadratic age‐related decrease in MTR began at about 40 years of age. Mean and standard deviation (SD) of MTR had the following decreasing order: thalamus (58.3 + 0.8), pallidus (56.8 ± 1.3), caudate (55.5 ± 1.6) and putamen (54.6 ± 1.1); temporal (56.8 ± 0.9), parietal‐insular (56.8 ± 1.1), frontal (56.5 ± 1.1), occipital (55.4 ± 1.0) and cerebellar (53.2 ± 1.0) cortex. In post‐hoc testing, all regional pairwise differences were statistically significant except pallidus vs. temporal or parietal‐insular cortex, caudate vs. occipital cortex, frontal vs. parietal‐insular or temporal cortex. Conclusion MTR of the cortical and subcortical brain GM structures decreases quadratically after midlife and shows significant regional differences. J. Magn. Reson. Imaging 2014;40:360–366 © 2013 Wiley Periodicals, Inc.